2019
DOI: 10.1192/bjp.2019.216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parental mental illness on children's physical health: systematic review and meta-analysis

Abstract: BackgroundChildren of parents with mental disorder face multiple challenges.AimsTo summarise evidence about parental mental disorder and child physical health.MethodWe searched seven databases for cohort or case–control studies quantifying associations between parental mental disorders (substance use, psychotic, mood, anxiety, obsessive–compulsive, post-traumatic stress and eating) and offspring physical health. Studies were excluded if: they reported perinatal outcomes only (<28 days) or outcomes after age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
118
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(127 citation statements)
references
References 84 publications
(186 reference statements)
7
118
0
2
Order By: Relevance
“…Third, children of parents with poor mental health might be more likely to have poor health. This has been con rmed by a recent systematic review and metaanalysis [16]. A Danish study found a higher use of primary healthcare as well as a higher rate of positive tests (C-reactive protein, Strep A test, Urinary stix) in children of mothers with depression which could be interpreted as a higher rate of infectious disease [2].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Third, children of parents with poor mental health might be more likely to have poor health. This has been con rmed by a recent systematic review and metaanalysis [16]. A Danish study found a higher use of primary healthcare as well as a higher rate of positive tests (C-reactive protein, Strep A test, Urinary stix) in children of mothers with depression which could be interpreted as a higher rate of infectious disease [2].…”
Section: Discussionmentioning
confidence: 80%
“…This study showed an association between paternal mental health condition and the use of healthcare services by a child younger than 12 months. This highlights the important role of the father's mental health which is often overlooked in research [16] and in society generally [39].…”
Section: Implications For Policy Practice and Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The main focus of the previous meta-analysis is to explore the effects of parental mental illness on children's physical health, after the research, they revealed that prenatal mental disorder had contributed to the poor fetal growth which further suggested that the impact of the maternal psychotic disease during pregnancy on children [34]. To compare with the previous study, more attention is being paid to the impact of maternal mental health during pregnancy on childhood systemic autoimmune diseases by the present meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…the offspring's proper development and growth (9)(10)(11)(12) . Previous reviews of the literature on this matter have not been able to reach any conclusions regarding data on the growth and body composition of the offspring of mothers with depressive symptoms (13)(14)(15) . Weight-and heightdeficient growth have been observed over the first year of life among the children of depressed mothers, while linear growth is possibly impaired for up to 5 years after birth (13) .…”
mentioning
confidence: 98%